Agricultural innovation policies: Prioritizing investments and promoting uptake and impacts at scale - Ragasa, Catherine; Spielman, David J.; Lynam, John K. (International Food Policy Research Institute, 2025)
Technological progress in agriculture is essential to tackling the many challenges facing food systems, but it has been unevenly distributed around the world, along with the accompanying gains in productivity and welfare. This chapter reviews the evolution of research on technical change and public policy, from seminal economic analyses highlighting the importance of technical change, to innovation systems analyses that broadened our understanding of the technical change process, on to the latest strategies being pursued to accelerate change.